Effectiveness of a multidisciplinary pulmonary rehabilitation program at Ewha Womans University Mokdong Hospital, Korea - Soo Jeong Han; Jee Hyun Suh (The Ewha Medical Journal)
Objectives: This study aimed to evaluate the effectiveness of a multidisciplinary pulmonary rehabilitation program at Ewha Womans University Mokdong Hospital, Korea that was designed to augment respiratory function, promote patient recovery, and improve discharge outcomes. Methods: This study was conducted as part of quality improvement activities from March to August 2023. A multidisciplinary pulmonary rehabilitation team was established, comprising specialists in rehabilitation medicine, pulmonology, and thoracic surgery, as well as physical and occupational therapists, and the nutrition team. We developed a comprehensive rehabilitation program that included stretching, strengthening exercises, aerobic training, and respiratory retraining, supplemented by individualized treatments such as bedside and ambulatory physical therapy. Evaluations before and after rehabilitation were performed using the Modified Medical Research Council Dyspnea Scale and the Chronic Obstructive Pulmonary Disease Assessment Test. The primary indicators of success were an increase of over 10% in pulmonary rehabilitation consultations and an improvement in discharge-to-home rates. Results: The total number of pulmonary rehabilitation cases rose by 79.16%, from 24 to 43, while consultations saw a 21.15% increase, from 52 to 63. Of the 63 pulmonary rehabilitation cases, 32 (50.8%) were transferred to other hospitals, 25 (39.7%) were discharged home, and 6 (9.5%) remained hospitalized. Conclusion: The study demonstrated the effectiveness of a multidisciplinary pulmonary rehabilitation approach in improving program participation and achieving meaningful discharge outcomes. These findings underscore the potential for expanding multidisciplinary efforts and highlight the need for further studies to increase discharge-to-home rates and evaluate the long-term impacts of such programs.